Review and development of environmental interpretation resources to foster environmental learning in two Kenyan schools - Atiti, Abel Barasa (Rhodes University, Faculty of Education, Department of Education, 2003)
This participatory action research study involved a group of teachers in transforming school grounds into interpretation resources. Approached from a critical perspective, it challenged the conventional top-down approaches to interpretation resources and materials development. Through a teacher-centred approach, a school-based 'botanic garden' and 'arboretum' were developed at Samaj and Kenya High respectively. Teachers were further actively engaged in developing a variety of interpretive materials that might engage learners in socially critical environmental education processes at the transformed sites. A process in which educators from five non-formal education organisations shared their skills and knowledge on environmental interpretation with teachers preceded the development of interpretation resources and materials. Drawing on Latour (1999), I have applied the notion of mobilising interpretive capital when describing this process. Interpretive capital within the non-formal education sector was mobilised and made available through social interactions between teachers and non-formal educators. This occurred during workshops, organisational visits and critical reviews of a sample of interpretive materials. I provide insights into how the interpretive capital was mobilised and later drawn on by teachers during the development processes in their schools. This study argues that mobilising interpretive capital with teachers through partnerships can enhance the transformation of school grounds to foster environmental learning. It shows how attempts to find solutions with teachers were made in response to pedagogical and curriculum tensions that arise around the implementation of environmental education processes in their schools. To provide orientation in environmental education processes in schools, analyses of socially critical environmental education processes and a review of theoretical perspectives on interpretation as an environmental education process are presented. I have viewed interpretation and environmental education as reciprocally necessary aspects for enabling the development of critical environmental literacy and action competence. To explain this view, the notion of environmental interpretation and education processes has been applied and presented in this study. Finally, practical outcomes of the study on transformation of school grounds, improved education practice, enhanced professional competencies amongst teachers, new interpretive materials in schools and the establishment of partnerships are examined.
Keywords: Environmental education -- Kenya; Environmental education -- Kenya -- Case studies